Myostatin: a potential therapeutic target for metabolic syndrome - Yang, Ming; Liu, Chongbin; Jiang, Na; Liu, Yan; Luo, Shilu; Li, Chenrui; Zhao, Hao; Han, Yachun; Chen, Wei; Li, Li; Xiao, Li; Sun, Lin (Frontiers in Endocrinology, 2023)
Metabolic syndrome is a complex metabolic disorder, its main clinical manifestations are obesity, hyperglycemia, hypertension and hyperlipidemia. Although metabolic syndrome has been the focus of research in recent decades, it has been proposed that the occurrence and development of metabolic syndrome is related to pathophysiological processes such as insulin resistance, adipose tissue dysfunction and chronic inflammation, but there is still a lack of favorable clinical prevention and treatment measures for metabolic syndrome. Multiple studies have shown that myostatin (MSTN), a member of the TGF-β family, is involved in the development and development of obesity, hyperlipidemia, diabetes, and hypertension (clinical manifestations of metabolic syndrome), and thus may be a potential therapeutic target for metabolic syndrome. In this review, we describe the transcriptional regulation and receptor binding pathway of MSTN, then introduce the role of MSTN in regulating mitochondrial function and autophagy, review the research progress of MSTN in metabolic syndrome. Finally summarize some MSTN inhibitors under clinical trial and proposed the use of MSTN inhibitor as a potential target for the treatment of metabolic syndrome.